Bosonic D-branes at finite temperature with an external field - Abdalla, MCB; Gadelha, A. L.; Vancea, IV (American Physical Soc, 2001)
Bosonic boundary states at finite temperature are constructed as solutions of boundary conditions at T not equal0 for bosonic open strings with a constant gauge field F-ab coupled to the boundary. The construction is done in the framework of ther-mo field dynamics where a thermal Bogoliubov transformation maps states and operators to finite temperature. Boundary states are given in terms of states from the direct product space between the Fock space of the closed string and another identical copy of it. By analogy with zero temperature, the boundary states have the interpretation of Dp-branes at finite temperature. The boundary conditions admit two different solutions. The entropy of the closed string in a Dp-brane state is computed and analyzed. It is interpreted as the entropy of the Dp-brane at finite temperature.